Content Creators as Employees: Role Design, Performance Measurement, and Strategic Impact on Organization - Gunawan, Ocha; Arifianto, Chandra Fitra (Science Tech Group, 2025)
This study aims to analyze the role of content creators as permanent employees in a Sharia-compliant automotive trading company in Bogor, and to assess how their performance is measured and its impact on organizational strategy. The research method used is a case study with a qualitative approach. Data were collected through in-depth interviews, observations, and documentation with nine content creators and a branch manager. Data validation was carried out using triangulation and member checking. The results show that content creators play a central role in increasing audience engagement and brand awareness through content planning, creative production, and interaction strategies. In addition, the contribution of content creators strengthens the company's competitiveness by adapting data-driven digital marketing strategies. This study has important implications for the digital marketing and human resource management literature and supports the Sustainable Development Goals (SDG 8: Decent Work and Economic Growth, and SDG 9: Industry, Innovation, and Infrastructure).